Yeast culture as an additive in swine grower rations - B A Koch; G L Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1975)
Adding yeast culture at manufacturer's recommended levels to a complete, pelleted, 16% crude protein ration fed to nursery-age pigs produced no measurable improvement in rate of gain, feed efficiency, survival, activity, or appearance.; Swine Day, Manhattan, KS, November 13, 1975
Keywords: Swine day; 1975; Kansas Agricultural Experiment Station contribution; no. 505; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 283; Swine; Yeast; Grower rations; Nursery pigs